Leveraging the gel-to-sol transition of physically crosslinked thermoresponsive polymer hydrogels to enable reactions induced by lowering temperature. Issue 34 (9th August 2022) - Lobban, Romario; Biswas, Ankan; Ruiz-Márquez, Kevin J.; Bellan, Leon M.
Abstract : The gel-to-sol transition that occurs when physically crosslinked thermoresponsive hydrogels are cooled below their solution point can be used to reliably trigger reactions between reagents embedded within. Abstract : Much work has been done on the use of heating to trigger reactions via the temperature-dependent removal of a barrier or constraint separating reagents. Far less work, however, has been done on the use of cooling to achieve a similar goal. Numerous applications, such as those involving components or materials susceptible to persistent low temperatures and cases in which energy for heating is not available, would benefit from this inverse approach. Hence, in this study we explore whether physically crosslinked hydrogels can be reliably used as thermoresponsive constraints that allow reagents to react only upon cooling. We achieve this by loading reagents into adjacent blocks of thermoresponsive hydrogel and showing that these reagents can only react with each other after the temperature of the hydrogel falls below its lower critical solution temperature (LCST). Above the LCST, the reagents remain sequestered in separate gels and no reaction occurs; this "OFF" state is stable for extended periods. When the system is allowed to cool, the hydrogels liquify and flow into each other, allowing mixing of the embedded reagents ("ON" state). We tune the hydrogels' LCSTs using NaCl, quantify the NaCl's tuning effect using rheometry, and determine that reactions are triggered reproducibly at temperatures similar to the tuned LCSTs. We also demonstrate generalizability of the concept by exploring situations involving radically different reaction types. This concept therefore constitutes a new approach to autonomous material behavior based on cooling.